A new distribution model with two-parameter - Bugatekin, Ayse Turan (Mustafa BAYRAM, 2017)
This paper deals with a two-parameter new mix distribution called as RL (Rayleigh- Logarithmic) distribution with increasing failure rate. Firstly, probability density function, distribution function, r th moment, survival and hazard functions of this two-parameter RL distribution are examined. Then, estimation of parameters by using standard statistical techniques such as maximum likelihood method and entropy are given for the new mix model. In the application part, a real data set is receipted and when RL distribution compared with other distributions, this RL distribution is shown be a good competitor.